Inequality and growth in neo-Kaleckian and Cambridge growth theory - Thomas I. Palley (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2016)
This paper examines the relationship between inequality and growth in the neo-Kaleckian and Cambridge growth models. The paper explores the channels whereby functional and personal income distribution impact growth. The growth - inequality relationship can be negative or positive, depending on the economy's characteristics. Contrary to widespread claims, inequality per se does not impact growth through macroeconomic channels. Instead, both growth and inequality are impacted by changes in the underlying forms and pattern of income payments. However, inequality is critical at the microeconomic level as it explains differences in household propensities to consume which are at the foundation of neo-Kaleckian and Cambridge growth theory. – – Dieses Working Paper behandelt die Beziehungen zwischen Ungleichheit und Wachstum in Neo-Kaleckianischen und Cambridge-Wachstumsmodellen. Dabei werden insbesondere die Transmissionskanäle untersucht, über die die funktionale und individuelle Einkommensverteilung das Wirtschaftswachstum beeinflussen. Die Beziehung zwischen Wachstum und Ungleichheit kann dabei, abhängig von den jeweiligen Charakteristika der Volkswirtschaft, positiv oder negativ sein. Entgegen weitverbreiteter Behauptungen hat Ungleichheit per se keinen direkten Einfluss auf das Wirtschaftswachstum über makroökonomische Transmissionskanäle. Stattdessen werden sowohl Ungleichheit als auch Wachstum von Veränderungen in den zugrundeliegenden Formen und Mustern von Einkommenszahlungen beeinflusst. Auf der mikroökonomischen Ebene ist Ungleichheit allerdings eine entscheidende Größe, da sie Unterschiede in den Konsumneigungen der Haushalte erklären kann, die die Grundlage der Neo-Kaleckianischen und Cambridge-Wachstumstheorie bilden.
urn:nbn:de:101:1-20160613770
Keywords: E0; E12; E25; 330; income inequality; growth; neo-Kaleckian theory; Cambridge growth theory